Embedded real-time system for detecting leakage of the gas used in iraqi kitchens - Husam Kareem (Institute of Advanced Engineering and Science, 2019)
A major issue that happens in kitchens of houses and/or restaurants is the leakage of gas used as a fuel for cooker stove, which is commonly referred to as LPG (liquefied petroleum gas). LPG leakage may lead to a serious fire or even a deadly explosion that might affect the surrounding people. A substantial solution to avoid such disasters is by stopping its main cause. Therefore designing a device capable of monitoring and detecting such gases can minimize the dangerous and unwanted incidents by LPG leakage. This paper introduces a low cost and energy efficient real-time monitoring system that able to sense different dangerous gases, specifically those used for stove cooker. This system considers the pros of the previously introduced systems and fixes the cons available in those systems. In addition, the manufacturing cost has been taken into consideration. If the system senses any type of LPG gas (there is a gas leakage), it will react by making three different actions. It will make an alert sound to notify the people around the leakage place, send an SMS to two cell phones, and show, on an LCD screen, the leakage location.